Implementation of PHPUnit-Based Test Driven Development in PharmacyERP System Development - Cahyani, Silvia Dwi; Anggraeny, Fetty Tri; Nurlaili, Afina Lina (LPPM Universitas Bina Sarana Informatika, 2026)
This research applies the Test-Driven Development (TDD) methodology using PHPUnit to develop an ERP system for Apotek Pasyha using the Laravel 12 framework. Through a case study design and Red-GreenRefactor cycles, the development of eight core modules yielded 751 test cases and 2,146 assertions. System success was measured using the Test Pass Rate, achieving an